Pengaruh Social Media Marketing dan Influencer Marketing Terhadap Keputusan Pembelian Konsumen Produk Skincare Azarine di Universitas Kristen Maranatha - Purba, Deva Giovani; Nurbasari, Anny (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
In the midst of competition with various local and even international skincare brands, Azarine develops and carries out In the midst of competition with various local and international skincare brands, Azarine develops and implements various marketing strategies to influence consumer purchase decisions. The objective of this study is to examine the impact of social media marketing and influencer marketing on purchasing decisions for Azarine skincare products at Universitas Kristen Maranatha. This research adopts a quantitative approach. The population consists of students from Universitas Kristen Maranatha. The target population includes both male and female students who have purchased Azarine products. Data collection involved distributing survey questionnaires via Google Forms. The obtained data will be analyzed using Smart PLS software. The findings of this study indicate that social media marketing positively influences purchase decisions. Influencer marketing also exerts a strong positive influence on purchase decisions. Moreover, these two marketing factors complement each other in positively influencing purchase decisions.